Cyclolinopeptide B methanol trisolvate - Schatte, Gabriele (International Union of Crystallography, 2011)
The title compound, C(56)H(83)N(9)O(9)S·3CH(3)OH, is a methanol trisolvate of the cyclolinopeptide cyclo(Met(1)—Leu(2)—Ile(3)—Pro(4)—Pro(5)—Phe(6)—Phe(7)—Val(8)—Ile(9)) (henceforth referred to as CLP-B), which was isolated from flaxseed oil. All the amino acid residues are in an l-configuration based on the CORN rule. The cyclic nonapeptide exhibits eight trans peptide bonds and one cis peptide bond observed between the two proline residues. The conformation is stabilized by an α-turn and two consecutive β-turns each containing a N—H⋯O hydrogen bond between the carbonyl group O atom of the first residue and the amide group H atom of the fourth (α-turn) or the third residue (β-turns), repectively. In the crystal, the components of the structure are linked by N—H⋯O and O—H⋯O hydrogen bonds into chains parallel to the a axis.